LANDASAN AGAMA DALAM PENDIDIKAN PUBERTAS DI SEKOLAH DASAR - Erry Utomo; Nurfadhilah Nurfadhilah; Agung Purwanto; Jatu Wahyu Wicaksono; Alrahmat Arif (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2019)
Abstract. Indonesia is experiencing a demographic bonus, and a good education and health situation will determine the quality of human resources so that this situation does not turn into a demographic burden or disaster. The Indonesian Adolescent Reproductive Health Survey shows the in-depth knowledge of adolescents about puberty, whereas adolescence is a golden period that will determine the quality of the next generation. This study aims to get a picture of the perception of teachers and students in particular about puberty and its relation to religion. The approach used is qualitative, data collected by conducting in-depth interviews with teachers, parents, and students. There were ten informants, consisting of teachers, parents, and students from 2 public and religious-based elementary schools in North Jakarta. In general, teachers have low knowledge / understanding of puberty, as well as students' knowledge. Most teachers have the perception that education about puberty in the classroom, according to the curriculum, turns out to be too vulgar so that some information is not conveyed to students. Religion is considered as the most reliable foundation in shaping student behavior. Teachers tend to hand over responsibility to religious teachers to deliver material on puberty, at religiously-based schools specifically mentioned teachers of fiqh. Teacher capacity building is needed regarding the material that must be taught, and it is delivery methods to suit the needs of students and have an impact on improving knowledge and improving behavior.Abstrak. Indonesia sedang mengalami bonus demografi dan situasi pendidikan dan kesehatan yang baik sangat menentukan kualitas sumber daya insani agar situasi ini tidak berbalik menjadi beban atau bencana demografi. Survei Kesehatan Reproduksi Remaja Indonesia memperlihatkan rendahnya pengetahuan remaja tentang pubertas, padahal masa remaja merupakan periode emas yang akan menentukan kualitas generasi berikutnya. Penelitian ini bertujuan mendapatkan gambaran persepsi guru dan peserta didik di khususnya tentang pubertas dan kaitannya dengan agama. Pendekatan yang digunakan yaitu kualitatif, data dikumpulkan dengan melakukan wawancara mendalam kepada guru, orang tua, dan peserta didik. Jumlah informan 10 orang, terdiri dari guru, orang tua, dan peserta didik dari 2 sekolah dasar umum dan berbasis agama di Jakarta Utara. Secara umum guru memiliki pengetahuan/pemahaman yang rendah tentang pubertas, demikian pula pengetahuan peserta didik. Kebanyakan guru memiliki persepsi bahwa edukasi tentang pubertas di kelas sesuai kurikulum ternyata dianggap terlalu vulgar sehingga sebagian informasi tidak disampaikan kepada peserta didik. Agama dianggap sebagai landasan paling diandalkan dalam membentuk perilaku peserta didik. Guru cenderung menyerahkan tanggung jawab kepada guru agama untuk menyampaikan materi tentang pubertas, pada sekolah berbasis agama disebutkan secara spesifik guru fiqih. Dibutuhkan pengembangan kapasitas guru tentang materi yang harus diajarkan dan metode penyampaiannya agar sesuai dengan kebutuhan peserta didik dan berdampak terhadap peningkatan pengetahuan serta perbaikan perilaku.